2017
DOI: 10.1097/ijg.0000000000000517
|View full text |Cite
|
Sign up to set email alerts
|

The Fluctuation of Intraocular Pressure Measured by a Contact Lens Sensor in Normal-Tension Glaucoma Patients and Nonglaucoma Subjects

Abstract: The range of IOP fluctuation was larger in the eyes with NTG than in the nonglaucoma eyes. This larger fluctuation might be one of the reasons underlying the aggravation of the visual field by NTG. Measurements of 24-hour continuous IOP might be one of the useful methods to distinguish NTG from nonglaucoma eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 26 publications
4
54
0
1
Order By: Relevance
“…The results suggested a trend towards a higher-amplitude IOP-related profile and faster rates of change in the visual field, although using an α level of 0.05, this was not statistically significant ( p = 0.053). We did, however, find that 13 of 22 eyes (59.1%) had a peak IOP-related profile during nocturnal hours, in agreement with previous studies showing that the majority of patients have a peak IOP at night [2,23,24] , and very similar to a previous study that found 57.1% of patients with NTG to have nocturnal IOP peaks [25] . Although aqueous production decreases during sleep, the nocturnal rise in IOP has been attributed to reduced aqueous outflow, partly due to a recumbent position during sleep, coupled with increased episcleral venous pressure [13,19,24,26] .…”
Section: Discussionsupporting
confidence: 81%
“…The results suggested a trend towards a higher-amplitude IOP-related profile and faster rates of change in the visual field, although using an α level of 0.05, this was not statistically significant ( p = 0.053). We did, however, find that 13 of 22 eyes (59.1%) had a peak IOP-related profile during nocturnal hours, in agreement with previous studies showing that the majority of patients have a peak IOP at night [2,23,24] , and very similar to a previous study that found 57.1% of patients with NTG to have nocturnal IOP peaks [25] . Although aqueous production decreases during sleep, the nocturnal rise in IOP has been attributed to reduced aqueous outflow, partly due to a recumbent position during sleep, coupled with increased episcleral venous pressure [13,19,24,26] .…”
Section: Discussionsupporting
confidence: 81%
“…Most importantly, the magnitude of change in IOP, rather than absolute IOP, appears to be of greater import for disease etiology in both animal models and human patients. In humans, IOP fluctuations, defined as the difference between the highest and lowest IOP, is greater in glaucoma patients than non-glaucoma patients (Nouri-Mahdavi et al, 2004; Sihota et al, 2005; De Moraes et al, 2011; Tan et al, 2017; Tojo et al, 2017) and is predictive of glaucoma progression (Nouri-Mahdavi et al, 2004; Sihota et al, 2005). Likewise, the magnitude of peak IOP measurement predicts progression in glaucoma patients, even for those with IOP successfully lowered by conventional treatments (Nouri-Mahdavi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Transient blurred vision, conjunctival hyperemia, and superficial punctate keratitis are the most frequent complications associated with Triggerfish CLS wear, as demonstrated by a number of clinical studies 812. Although no serious adverse events have been reported to be associated with the wear of the Triggerfish CLS, mild adverse effects are common.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Tojo et al performed 24-hour CLS monitoring in 14 NTG subjects and 12 healthy individuals 12. Significantly higher ranges of CLS output were observed in NTG patients compared to controls over the entire 24-hour observation period, as well as during diurnal and nocturnal periods when analyzed individually.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation